PPAT Reformulation in Electronically Integrated Registration of Mortgage Rights - Pamungkas, Bagus Satria; Djunaedi, Djunaedi (Jurnal Konstatering, 2023)
Mortgage is a guarantee for land that is registered online at the National Land Agency. PPAT reformulation is important so that data is guaranteed to be accurate. PPAT examines documents, draws up deeds, and submits registration to BPN. PPAT is responsible for the validity of documents. Registration of electronic Mortgage is faster, more efficient and safer because it is connected to the database. The research method used is normative law, viewing law as a system of norms. This research includes principles, norms, rules, court decisions, agreements, and doctrine. Normative legal research aims to find rules, principles, and doctrines to answer legal problems. This research is descriptive-analytical in nature, providing an overview and assessment of PPAT reformulation in integrated mortgage registration. The Electronic Mortgage System is the registration and maintenance of land data through an integrated electronic system. Registered user meets the requirements, application is accepted. PPAT and banks are responsible. Mortgage rights involve guarantees for property, business use, building, and usage rights. Electronic registration according to the rules. PPAT constraints: user requirements, certificates at the OJK, debtor certificates, credit syndication arrangements, and creditor registration obligations. PPAT ensures data accuracy. PPAT Constraints in electronic Mortgage registration: Registered user requirements impede access, Requirements for registered letters at the OJK limit the choice of creditors, Requirements for certificates in the name of the debtor are contrary to UUHT. There is no registration mechanism in a credit syndication, Registration obligation is the responsibility creditor, not PPAT. Keywords: Electronic; Mortgage; Reformulation.